Preparation method of iron-manganese bimetallic single atom-loaded nitrogen-doped carbon sphere catalyst

The preparation of iron-manganese bimetallic single-atom supported nitrogen-doped carbon sphere catalysts was solved by combining hydrothermal method and calcination method, and the problems of low loading of single-atom catalysts and single active sites were solved, achieving efficient activation of PMS and significantly improving the pollutant degradation efficiency.

CN117019197BInactive Publication Date: 2025-04-08EAST CHINA UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310989317.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-08
Publication Date
2025-04-08
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When existing single-atom catalysts catalytically activate persulfate to degrade pollutants, there are problems such as low loading, single active sites and unstable catalytic performance.

Method used

A combination of hydrothermal method and calcination method was used to prepare a single-atom supported nitrogen-doped carbon spheric catalyst of iron and manganese bimetallic bimetallic. The single-atom iron and single-atom manganese were successfully connected to the surface of carbon nitride to maintain the spherical morphology, and a diatom catalyst was formed by calcination.

Benefits of technology

The efficient activation of PMS was achieved, which significantly improved the degradation efficiency of emerging organic pollutants, and was able to completely degrade 10 mg/L of PCMX solution within 1 minute, and the stability and catalytic performance of the catalyst were significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117019197B_ABST
    Figure CN117019197B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing an iron-manganese bimetallic single-atom-loaded nitrogen-doped carbon sphere catalyst, using dopamine hydrochloride and trihydroxymethylaminomethane, first hydrothermally synthesizing a specific morphology polydopamine carbon sphere by controlling process parameters, and adding a predetermined amount of anhydrous manganese sulfate and iron nitrate nine hydrates to introduce the iron-manganese bimetal, and then synthesizing a diatomic nitrogen-doped carbon sphere catalyst by calcination. The method controls the process parameters by a hydrothermal method to obtain a specific morphology polydopamine carbon sphere, and then combines it with a calcination method, while successfully connecting single-atom iron and single-atom manganese to the surface of carbon nitride, the specific morphology of the sphere is maintained, and a highly efficient and durable diatomic catalyst is successfully provided. And due to the successful introduction of single-atom iron and single-atom manganese, potassium persulfate composite salt (Oxone) can be efficiently activated to degrade chloro-meta-xylenol, and the product of the present invention can completely degrade a chloro-meta-xylenol solution with a concentration of 10 mg / L within 1 minute.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method and application of a Fe and Mn single atom-loaded nitrogen-doped carbon sphere catalyst. Background Art

[0002] In recent years, human life and industrial activities have caused new pollutants to spread widely in the environmental matrix. Although its content in the environment is very small, its potential hazards such as neurotoxicity and genotoxicity pose a serious threat to human health and ecological environmental safety, and have attracted widespread attention from researchers. Among the various treatment technologies for new pollutants, persulfate-based advanced oxidation processes (SR-AOPs) have shown obvious advantages in treatment efficiency and resistance to external environmental interference, and have gradually attracted attention. SR-AOPs rely on the oxygen-oxygen bond of persulfate to break under activation conditions such as heating, ultraviolet irradiation, alkali, carbon materials, ultrasound and transition metals to form sulfate radicals (SO4 ·- ) to degrade new pollutants in water. Among them, the activation method based on transition metals is simple and efficient, and is currently the most common activation method.

[0003] Transition metals have excellent redox ability. In 2004, Dionysiou et al. compared the activation efficiency of nine different transition metal ions such as silver, cobalt, iron, and manganese on PMS and PDS. They found that Co 2+ And Ru 2+ Among the above transition metal ions, Ag is the best transition metal ion for PDS activation. + However, compared with the other eight transition metal ions, the cost of Ag is the highest, and it is unrealistic to apply it on a large scale to activate PS to remove new pollutants. O (II) Although the activation effect is very good, C O (II) is highly toxic and is often difficult to use in actual water treatment projects. O Although Fe(II) is relatively poor in activating PMS compared to Fe(II), it is rich in iron, cheap and easy to obtain, less toxic to the environment, and has high biocompatibility. Therefore, from an application perspective, Fe(II) is more suitable for activating persulfate.

[0004] Single atom catalysts (SACs) refer to a special type of supported metal catalysts in which the metal active components are stabilized on the carrier by isolated single atoms. They are catalysts that transition from heterogeneous catalysts to homogeneous catalysts. Single atom catalysts emphasize the uniformity of dispersion. Due to the existence of surface heterogeneity of the carrier, that is, the chemical environment of each metal atom is different, the catalytic activity of each metal atom may be different. Single atom catalysts (SACs) have become a hot research field in the field of catalysis because they can utilize most metal sites and show excellent structural stability and catalytic activity. Related studies have shown that when unsaturated single metal atoms are used as active centers of catalytic reactions, the utilization rate of atoms can be greatly improved, and the homogeneity of single atom active sites makes them highly selective for certain reactions. Single-atom catalysts show good catalytic performance in the process of catalytic activation of persulfate for catalytic degradation of pollutants, but single-atom catalysts have some defects, such as: (a) low loading rate: due to the high surface free energy of individual metal atoms in single-atom catalysts, migration and agglomeration are very likely to occur during the production, preparation and catalytic reaction process, resulting in a decrease in the catalytic performance of the material; (b) single active site: limited by one active site, it is difficult to break the linear proportional relationship of the intermediates. In addition, SAC may be ineffective for some reactions that require adjacent active sites.

[0005] In this regard, the invention provides a method for preparing a nitrogen-doped carbon sphere catalyst, which uses dopamine hydrochloride and trihydroxymethylaminomethane to hydrothermally synthesize polydopamine carbon spheres with a specific morphology, and then adds anhydrous manganese sulfate and nonahydrated iron nitrate to introduce iron-manganese bimetallics, and then synthesizes diatomic nitrogen-doped carbon sphere catalysts by calcination. This method combines the hydrothermal method with the calcination method, successfully attaching single-atom iron and single-atom manganese to the surface of carbon nitride while maintaining the specific spherical morphology. A series of characterization methods have been used to prove that the material has good catalytic properties. The successful introduction of single-atom iron and single-atom manganese can efficiently activate PMS to degrade PCMX. The best sample Fe-Mn-NC-PDA completely degrades a PCMX solution with a concentration of 10 mg / L within 1 minute. Through capture experiments combined with EPR tests, the main active species in the system were explored as Fe(IV), •SO4 - and •OH also have certain oxidation contributions. Fe(II) on the Fe-Mn-NC-PDA surface effectively activates PMS to produce Fe(IV), selectively eliminating emerging organic pollutants. This part of the work provides a new idea for designing efficient and durable diatomic catalysts. Summary of the invention

[0006] The present invention provides a method for preparing an iron-manganese bimetallic single-atom loaded nitrogen-doped carbon sphere catalyst, using dopamine hydrochloride and trihydroxymethylaminomethane, first hydrothermally synthesizing a polydopamine carbon sphere with a specific morphology by controlling process parameters, and then adding a predetermined amount of anhydrous manganese sulfate and iron nitrate nonahydrate to introduce the iron-manganese bimetal, and then synthesizing a diatomic nitrogen-doped carbon sphere catalyst by calcination. The method controls the process parameters by a hydrothermal method to obtain a polydopamine carbon sphere with a specific morphology, and then combines it with a calcination method, while successfully connecting the single-atom iron and the single-atom manganese to the surface of carbon nitride, maintaining the specific morphology of the sphere, and successfully providing an efficient and durable diatomic catalyst. And due to the successful introduction of the single-atom iron and the single-atom manganese, potassium persulfate complex salt (Oxone) can be efficiently activated to degrade chloro-meta-xylenol, and the product of the present invention can completely degrade a 10 mg / L para-chloro-meta-xylenol solution within 1 minute. The specific scheme is as follows:

[0007] A method for preparing an iron-manganese bimetallic single atom-supported nitrogen-doped carbon sphere catalyst, comprising:

[0008] 1) Disperse tris(hydroxymethylaminomethane) in deionized water to obtain a solution, adjust the pH of the solution to 8.4-8.6 with HCl, and name the obtained liquid Tris solution, wherein the concentration of tris(hydroxymethylaminomethane) is 50-55 mM;

[0009] 2) Add a predetermined amount of dopamine hydrochloride to the Tris solution, wherein the mass and volume ratio of dopamine hydrochloride to the Tris solution is 1-2g:200ml, and heat under stirring. After the reaction is completed, wash the obtained sample with water and alcohol for several times, and dry it to obtain polydopamine powder;

[0010] 3) Weigh a predetermined mass of the above polydopamine powder and disperse it into deionized water, add a predetermined mass of anhydrous manganese sulfate and nonahydrate iron nitrate powder, wherein the ratio of polydopamine: anhydrous manganese sulfate: nonahydrate iron nitrate is 1g: 0.01mmol: 0.01-0.03mmol, mix well, centrifuge and remove the supernatant to obtain a solid sample, then freeze the sample for a predetermined time, and then freeze-dry in a vacuum freezer;

[0011] 4) Calcine the product of step 3 for a predetermined time under a protective atmosphere at a temperature of 800-850° C. to obtain an iron-manganese bimetallic single atom-supported nitrogen-doped carbon sphere catalyst.

[0012] Further, 6.057 g of tris(hydroxymethyl)aminomethane was weighed and dispersed into 1 L of deionized water, and the pH was adjusted to 8.5.

[0013] Further, 1.0 g of dopamine trihydrochloride was weighed and dispersed into 200 mL of Tris solution.

[0014] Furthermore, in step 2, the heating temperature is 34-36° C. and the heating time is 24-26 h.

[0015] Further, in step 3, vacuum drying is performed in a freeze dryer for 24-36 hours.

[0016] Furthermore, in step 4, the calcination is carried out in a tubular furnace under argon protection at a rate of 3°C / min to 800°C and kept at that temperature for 4 hours.

[0017] Furthermore, an iron-manganese bimetallic single atom-loaded nitrogen-doped carbon sphere catalyst is provided, wherein iron and manganese are loaded in the form of single atoms on the surface of nitrogen-doped carbon spheres obtained by thermal decomposition of polydopamine, characterized in that the catalyst is prepared by the preparation method described.

[0018] Furthermore, a method for catalyzing parachlorometaxylenol (PCMX) with the catalyst is provided, wherein the nitrogen-doped carbon sphere catalyst prepared by the above preparation method is placed in a container, and a parachlorometaxylenol solution is added to the container, and after stirring, PMS is added to degrade PCMX.

[0019] Further, 10-20 mg of the nitrogen-doped carbon sphere catalyst prepared by the above preparation method was weighed and placed in a beaker, and 49-51 ml of p-chloro-meta-xylenol solution was added to the beaker and stirred, and then 5-15 mg of PMS was added to degrade PCMX.

[0020] The present invention has the following beneficial effects:

[0021] 1) The present invention adjusts the concentration of dopamine hydrochloride to obtain spherical polydopamine particles with a specific size. The catalytic efficiency of the catalyst can be significantly improved at this size, and a bimetallic co-doped carbon nanocomposite material with uniform composition can be obtained only by a simple hydrothermal method plus a calcination method. The preparation method is simple and controllable, the reaction raw materials are easily available, the cost is low, and it has good prospects for industrial production.

[0022] 2) Iron-manganese bimetallic co-doping

[0023] The present invention develops a bimetallic atom-doped catalyst. Most single-atom catalysts still have the problems of cumbersome preparation, single single-atom active center, low loading rate, etc. The construction of bimetallic active center introduces another metal atom with strong catalytic activity on the single-metal atom catalyst, which can not only avoid the aggregation of metal atoms, improve the metal loading rate and catalyst stability, but also make the catalyst still have a high catalytic efficiency within a wide potential window. Compared with the catalysts anchored by single metal iron and single metal manganese, the catalytic effect is significantly improved, indicating that the iron-manganese bimetallic at a specific ratio plays a synergistic role, greatly improving the electron transfer efficiency, thereby improving the reaction rate.

[0024] 3) Since the drying is carried out in a frozen state, the volume of polydopamine remains almost unchanged, and the original spherical structure is maintained, and no concentration or spherical rupture occurs. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 TEM and SEM images of Fe-Mn-NC-PDA;

[0026] Figure 2 HRTEM image and mapping image of Fe-Mn-NC-PDA;

[0027] Figure 3 XRD pattern of Fe-Mn-NC-PDA;

[0028] Figure 4 (a, b) PCMX degradation curves of Fe-Mn-NC-PDA-1.0, Fe-Mn-NC-PDA-3.0, and Fe-Mn-NC-PDA-6.0 of different sizes and the corresponding first-order kinetic fitting diagrams;

[0029] Figure 5 (a, b) PCMX degradation curves of Fe-Mn-NC-PDA-1.0 under different pH conditions and the corresponding first-order kinetic fitting diagrams;

[0030] Figure 6 (a, b) PCMX degradation curves of Fe-Mn-NC-PDA-1.0 under different catalyst dosage conditions and the corresponding first-order kinetic fitting diagrams;

[0031] Figure 7 (a, b) PCMX degradation curves of Fe-Mn-NC-PDA-1.0 under different PMS dosage conditions and the corresponding first-order kinetic fitting diagrams;

[0032] Figure 8 (a, b) PCMX degradation curves of different systems and the corresponding first-order kinetic fitting diagrams;

[0033] Fig. 9 PCMX degradation curves of catalysts under different iron-manganese ratios;

[0034] Fig.10 EPR spectra of Fe-Mn-NC-PDA(1.0) and NC-PDA(1.0): DEPO-•O 2- (a), DEPO-•OH or DEPO-SO4 •- (b), and TEMP- 1 O2(c);

[0035] Fig.11The consumption of PMSO and the generation of PMSO2 in the Fe-Mn-NC-PDA (1.0) system;

[0036] Fig.12 Degradation pathway diagram of PCMX in Fe-Mn-PDA(1.0) / PMS system. DETAILED DESCRIPTION

[0037] The present invention will be described in more detail below through specific embodiments, but the protection scope of the present invention is not limited to these embodiments.

[0038] Example Preparation of nitrogen-doped carbon sphere catalyst.

[0039] Example 1

[0040] Weigh 1.0g dopamine hydrochloride and disperse it into 200mL Tris buffer solution with a concentration of 50mM and pH=8.5, and react for 24h in a 35℃ oil bath, avoid light, oxygen, and magnetic stirring at a certain speed. Then centrifuge the resulting solution at 9000r / min for 5min, remove the supernatant, wash with water and alcohol several times, and finally dry it in a vacuum constant temperature drying oven at 60℃ to obtain black PDA microsphere solid powder. Mix 0.01mmolMnSO4 and 0.01mmolFe(NO3)3•9H2O with 1gPDA in 20mL deionized water to make a solution, put it in an ultrasonic machine for 5min, then put it on a magnetic stirrer and stir it at an appropriate speed for 3min, and then put it in a centrifuge and centrifuge it at 10000r / min for 5min, remove the supernatant after taking it out, and then transfer the sample to a refrigerator for freezing for about 2h, and then vacuum dry it in a freeze dryer for 24h. After drying, take out the sample, take an appropriate amount of sample and place it in a porcelain boat, put it into a tube furnace, raise the temperature in the tube furnace to 800°C at a heating rate of 3°C / min, and calcine it for 4 hours by a one-step pyrolysis method in an argon flow at 800°C. After the calcination process, wait for it to cool naturally to room temperature, grind the obtained black sample thoroughly, and the final sample is marked as Fe-Mn-NC-PDA-1.0 (1:1).

[0041] Example 2

[0042] Weigh 2.0g dopamine hydrochloride and disperse it into 200mL Tris buffer solution with a concentration of 50mM and pH=8.5, and react for 24h in a 35℃ oil bath, avoid light, oxygen, and magnetic stirring at a certain speed. Then centrifuge the resulting solution at 9000r / min for 5min, remove the supernatant, wash with water and alcohol several times, and finally dry it in a vacuum constant temperature drying oven at 60℃ to obtain black PDA microsphere solid powder. Mix 0.01mmolMnSO4 and 0.01mmolFe(NO3)3•9H2O with 1gPDA in 20mL deionized water to make a solution, put it in an ultrasonic machine for 5min, then put it on a magnetic stirrer and stir it at an appropriate speed for 3min, and then put it in a centrifuge and centrifuge it at 10000r / min for 5min, remove the supernatant after taking it out, and then transfer the sample to a refrigerator for freezing for about 2h, and then vacuum dry it in a freeze dryer for 24h. After drying, take out the sample, take an appropriate amount of sample and place it in a porcelain boat, put it into a tube furnace, raise the temperature in the tube furnace to 800°C at a heating rate of 3°C / min, and calcine it for 4 hours by a one-step pyrolysis method in an argon flow at 800°C. After the calcination process, wait for it to cool naturally to room temperature, grind the obtained black sample thoroughly, and the final sample is marked as Fe-Mn-NC-PDA-2.0 (1:1).

[0043] Example 3

[0044] Weigh 1.0g dopamine hydrochloride and disperse it into 200mL Tris buffer solution with a concentration of 50mM and pH=8.5, and react for 24h in a 35℃ oil bath, avoid light, oxygen, and magnetic stirring at a certain speed. Then centrifuge the resulting solution at 9000r / min for 5min, remove the supernatant, wash with water and alcohol several times, and finally dry it in a vacuum constant temperature drying oven at 60℃ to obtain black PDA microsphere solid powder. Mix 0.01mmolMnSO4 and 0.03mmolFe(NO3)3•9H2O with 1gPDA in 20mL deionized water to make a solution, put it in an ultrasonic machine for 5min, then put it on a magnetic stirrer and stir it at an appropriate speed for 3min, and then put it in a centrifuge and centrifuge it at 10000r / min for 5min, remove the supernatant after taking it out, and then transfer the sample to a refrigerator for freezing for about 2h, and then vacuum dry it in a freeze dryer for 24h. After drying, take out the sample and place an appropriate amount of the sample in a porcelain boat, put it into a tube furnace, raise the temperature in the tube furnace to 800°C at a heating rate of 3°C / min, and calcine it for 4 hours by a one-step pyrolysis method in an argon flow at 800°C. After the calcination process, wait for it to cool naturally to room temperature, grind the obtained black sample thoroughly, and the final sample is marked as Fe-Mn-NC-PDA-1.0 (3:1).

[0045] Comparative Example 1

[0046] Weigh 3.0g dopamine hydrochloride and disperse it into 200mL Tris buffer solution with a concentration of 50mM and pH=8.5, and react for 24h in a 35℃ oil bath, avoid light, oxygen, and magnetic stirring at a certain speed. Then centrifuge the resulting solution at 9000r / min for 5min, remove the supernatant, wash with water and alcohol several times, and finally dry it in a vacuum constant temperature drying oven at 60℃ to obtain black PDA microsphere solid powder. Mix 0.01mmolMnSO4 and 0.01mmolFe(NO3)3•9H2O with 1gPDA in 20mL deionized water to make a solution, put it in an ultrasonic machine for 5min, then put it on a magnetic stirrer and stir it at an appropriate speed for 3min, and then put it in a centrifuge and centrifuge it at 10000r / min for 5min, remove the supernatant after taking it out, and then transfer the sample to a refrigerator for freezing for about 2h, and then vacuum dry it in a freeze dryer for 24h. After drying, take out an appropriate amount of sample and place it in a porcelain boat, put it into a tube furnace, raise the temperature in the tube furnace to 800°C at a heating rate of 3°C / min, and calcine it for 4 hours by a one-step pyrolysis method in an argon flow at 800°C. After the calcination process, wait for it to cool naturally to room temperature, grind the obtained black sample thoroughly, and the final sample is marked as Fe-Mn-NC-PDA-3.0 (1:1).

[0047] Comparative Example 2

[0048] Weigh 6.0g dopamine hydrochloride and disperse it into 200mL Tris buffer solution with a concentration of 50mM and pH=8.5, and react for 24h in a 35℃ oil bath, avoid light, oxygen, and magnetic stirring at a certain speed. Then centrifuge the resulting solution at 9000r / min for 5min, remove the supernatant, wash with water and alcohol several times, and finally dry it in a vacuum constant temperature drying oven at 60℃ to obtain black PDA microsphere solid powder. Mix 0.01mmolMnSO4 and 0.01mmolFe(NO3)3•9H2O with 1gPDA in 20mL deionized water to make a solution, put it in an ultrasonic machine for 5min, then put it on a magnetic stirrer and stir it at an appropriate speed for 3min, and then put it in a centrifuge and centrifuge it at 10000r / min for 5min, remove the supernatant after taking it out, and then transfer the sample to a refrigerator for freezing for about 2h, and then vacuum dry it in a freeze dryer for 24h. After drying, take out an appropriate amount of sample and place it in a porcelain boat, put it into a tube furnace, raise the temperature in the tube furnace to 800°C at a heating rate of 3°C / min, and calcine it for 4 hours by a one-step pyrolysis method in an argon flow at 800°C. After the calcination process, wait for it to cool naturally to room temperature, grind the obtained black sample thoroughly, and the final sample is marked as Fe-Mn-NC-PDA-6.0 (1:1).

[0049] Comparative Example 3

[0050] Weigh 1.0g dopamine hydrochloride and disperse it into 200mL Tris buffer solution with a concentration of 50mM and pH=8.5, and react for 24h in a 35℃ oil bath, avoid light, oxygen, and magnetic stirring at a certain speed. Then centrifuge the resulting solution at 9000r / min for 5min, remove the supernatant, wash with water and alcohol several times, and finally dry it in a vacuum constant temperature drying oven at 60℃ to obtain black PDA microsphere solid powder. Mix 0.03mmolMnSO4 and 0.01mmolFe(NO3)3•9H2O with 1gPDA in 20mL deionized water to make a solution, put it in an ultrasonic machine for 5min, then put it on a magnetic stirrer and stir it at an appropriate speed for 3min, and then put it in a centrifuge and centrifuge it at 10000r / min for 5min, remove the supernatant after taking it out, and then transfer the sample to a refrigerator for freezing for about 2h, and then vacuum dry it in a freeze dryer for 24h. After drying, take out the sample, take an appropriate amount of sample and place it in a porcelain boat, put it into a tube furnace, raise the temperature in the tube furnace to 800°C at a heating rate of 3°C / min, and calcine it for 4 hours by a one-step pyrolysis method in an argon flow at 800°C. After the calcination process, wait for it to cool naturally to room temperature, grind the obtained black sample thoroughly, and the final sample is marked as Fe-Mn-NC-PDA-1.0 (1:3).

[0051] Comparative Example 4

[0052] Preparation of Nitrogen-doped Carbon Spheres without Metal Anchoring

[0053] Weigh 1.0g dopamine hydrochloride and disperse it into 200mL Tris buffer solution with a concentration of 50mM and pH=8.5, and react for 24h in a 35℃ oil bath, avoid light, oxygen, and magnetic stirring at a certain speed. Then centrifuge the resulting solution at 9000r / min for 5min, remove the supernatant, wash with water and alcohol several times, and finally dry it in a 60℃ vacuum constant temperature drying oven to obtain black PDA microsphere solid powder. Take an appropriate amount of PDA powder and place it in a porcelain boat, put it in a tube furnace, raise the temperature in the tube furnace to 800℃ at a heating rate of 3℃ / min, and calcine it for 4h in an argon flow at 800℃ by a one-step pyrolysis method. After the calcination process is completed, let it cool naturally to room temperature, grind the obtained black sample fully, and the final sample is marked as NC-PDA-1.0.

[0054] Comparative Example 5

[0055] Preparation of Nitrogen-doped Carbon Spheres Anchored by Single Metallic Iron

[0056] Weigh 1.0g dopamine hydrochloride and disperse it into 200mL Tris buffer solution with a concentration of 50mM and pH=8.5, and react for 24h in a 35℃ oil bath, avoid light, oxygen, and magnetic stirring at a certain speed. Then centrifuge the resulting solution at 9000r / min for 5min, remove the supernatant, wash with water and alcohol several times, and finally dry it in a vacuum constant temperature drying oven at 60℃ to obtain black PDA microsphere solid powder. Mix 0.01mmolFe(NO3)3•9H2O and 1gPDA in 20mL deionized water to make a solution, put it in an ultrasonic machine for 5min, then put it on a magnetic stirrer and stir it at an appropriate speed for 3min, and then put it in a centrifuge and centrifuge it at 10000r / min for 5min, remove the supernatant after taking it out, and then transfer the sample to a refrigerator to freeze for about 2h, and then vacuum dry it in a freeze dryer for 24h. After drying, take out the sample and place an appropriate amount of the sample in a porcelain boat, put it into a tubular furnace, raise the temperature in the tubular furnace to 800°C at a heating rate of 3°C / min, and calcine it for 4 hours by a one-step pyrolysis method in an argon flow at 800°C. After the calcination process, wait for it to cool naturally to room temperature, grind the obtained black sample thoroughly, and the final sample is marked as Fe-NC-PDA-1.0.

[0057] Comparative Example 6

[0058] Preparation of nitrogen-doped carbon spheres anchored by single metallic manganese

[0059] Weigh 1.0g dopamine hydrochloride and disperse it into 200mL Tris buffer solution with a concentration of 50mM and pH=8.5, and react for 24h in a 35℃ oil bath, avoid light, oxygen, and magnetic stirring at a certain speed. Then centrifuge the resulting solution at 9000r / min for 5min, remove the supernatant, wash with water and alcohol several times, and finally dry it in a vacuum constant temperature drying oven at 60℃ to obtain black PDA microsphere solid powder. Mix 0.01mmolMnSO4 and 1gPDA in 20mL deionized water to make a solution, put it in an ultrasonic machine for 5min, then put it on a magnetic stirrer and stir it at an appropriate speed for 3min, and then put it in a centrifuge and centrifuge it at 10000r / min for 5min, remove the supernatant after taking it out, and then transfer the sample to a refrigerator for about 2h, and then vacuum dry it in a freeze dryer for 24h. After drying, take out the sample and place an appropriate amount of the sample in a porcelain boat, put it into a tubular furnace, raise the temperature in the tubular furnace to 800°C at a heating rate of 3°C / min, and calcine it for 4 hours by a one-step pyrolysis method in an argon flow at 800°C. After the calcination process, wait for it to cool naturally to room temperature, grind the obtained black sample thoroughly, and the final sample is marked as Mn-NC-PDA-1.0.

[0060] Experiments and Data

[0061] 1. Activation of PMS to degrade PCMX

[0062] The catalytic performance of each catalyst was evaluated by the degradation rate of PCMX. 20 mg Fe-Mn-NC-PDA-1.0 was placed in a beaker, 50 mL PCMX solution was added, and the mixture was evenly dispersed and mixed in an ultrasonic machine. The mixture was continuously stirred to reach adsorption-desorption equilibrium, and then 15 mg PMS was added to degrade PCMX. During the experiment, 1.2 mL of sample was taken with a dropper at fixed intervals, placed in a syringe equipped with a 0.22 μm hydrophilic PTFE needle filter, quickly injected into a centrifuge tube, and 1 mL of sample was transferred to a liquid phase vial containing 1 mL methanol with a pipette, and the PCMX concentration was determined by high-resolution liquid chromatography. The detection conditions are: the injection volume is 1 μL, the mobile phase consists of 80% methanol and 20% ultrapure water, and the rate is 1.0 mL / min.

[0063] Table 1. Reaction rate of PCMX degradation by Oxone activated by different catalysts

[0064] catalyst <![CDATA[Reaction rate (s -1 ).]]> Fe-Mn-NC-PDA-1.0(1:1) 0.02275 Fe-Mn-NC-PDA-2.0(1:1) 0.0184 Fe-Mn-NC-PDA-1.0(3:1) 0.0158 Fe-Mn-NC-PDA-3.0(1:1) 0.00742 Fe-Mn-NC-PDA-6.0(1:1) 0.00384 Fe-Mn-NC-PDA-1.0(1:3) 0.008 NC-PDA-1.0 0 Fe-NC-PDA-1.0 0.0053 Mn-NC-PDA-1.0 0.0036

[0065] 2. Physicochemical properties of Fe-Mn-NC-PDA

[0066] In the process of preparing the series of Fe-Mn-NC-PDA, the metal and polydopamine are first attached together through simple solution mixing, and then the sample is centrifuged and washed with water several times, dried and then calcined to obtain carbon nitride.

[0067] like Figure 1 The nitrogen-doped carbon spheres present a spherical structure ( Figure 1 ). By changing the concentration of dopamine hydrochloride, the precursor of nitrogen-doped carbon spheres, the size of the carbon spheres can be adjusted within the diameter range of 200nm-1μm. Figure 2 We can see that even at high magnification, the iron and manganese metals anchored on the catalyst are still not visible. Therefore, it can be inferred that the iron and manganese are anchored on the catalyst in the form of single atoms, and the element mapping diagram shows that the iron and manganese elements are evenly distributed on the catalyst.

[0068] In the XRD spectrum ( Figure 3 ), all samples were o 46 o There are two characteristic diffraction peaks at each location, which correspond to the (002) and (101) planes of carbon nitride, respectively. No other impurity peaks were observed, indicating that the main chemical structure did not undergo major changes during the calcination process. Combined with the above characterization, we can conclude that the iron / manganese diatomic structure was successfully constructed on NC-PDA, and no metal aggregation or nanoparticles were observed.

[0069] Depend on Figure 1 It can be seen that nitrogen-doped carbon spheres of different sizes were successfully prepared by adjusting the concentration of dopamine hydrochloride. Figure 2 The HRTEM image shows that there is no particle accumulation on the catalyst surface, and the corresponding mapping image shows that the three elements of iron, manganese and nitrogen are evenly distributed on the catalyst surface. Figure 3 The XRD patterns show that the three Fe-Mn-NC-PDAs with different sizes have similar peak shapes to the PDA without iron and manganese elements, that is, only the convolution of the carbon peak, which further proves that the loaded iron and manganese are anchored on the catalyst surface in the form of single atoms.

[0070] 1. Catalytic mechanism of Fe-Mn-NC-PDA

[0071] The first thing to explore is the effect of catalyst size on the degradation effect. Figure 4 It shows that the Fe-Mn-NC-PDA (1.0) system is more efficient in degrading PCMX. It has completed 100% degradation of PCMX in 5 minutes. At 2 minutes, the PCMX concentration has dropped to 6% of the initial value, and the degradation is almost complete. Compared with the Fe-Mn-NC-PDA (3.0) and Fe-Mn-NC-PDA (6.0) systems, the degradation rate of the Fe-Mn-NC-PDA (1.0) system is much better than that of the Fe-Mn-PDA (3.0) and Fe-Mn-PDA (6.0) systems before 30 seconds. The reason why Fe-Mn-NC-PDA (1.0) has better performance may be that Fe-Mn-NC-PDA (1.0) has better dispersibility in PCMX solution and Fe-Mn-NC-PDA (1.0) has a smaller geometric scale, a larger specific surface area, and better adsorption, which makes it more effective when loaded with iron and manganese, and thus has better catalytic performance. Then the effect of pH on the degradation performance was investigated. Figure 5 It can be seen that when the PCMX pollutant solution is adjusted to pH = 3, the Fe-Mn-NC-PDA (1.0) system has the best degradation effect, 96% of the PCMX pollutant has been degraded in 30s, and 100% of PCMX has been degraded in 60s. With the increase of pH value, the effect of Fe-Mn-NC-PDA (1.0) catalyzing PMS to degrade PCMX gradually weakens, but it can also complete the degradation of pollutants in a short time, indicating that the system can adapt to the degradation environment of pH value in a wide range.

[0072] We also investigated the effects of catalyst and PMS dosage on the degradation effect. Figure 6,7 It can be seen that the larger the catalyst dosage, the better the effect. However, when the dosage of PMS plays a role in the degradation of PCMX, the degradation effect is not necessarily better with the dosage. When the dosage of PMS increases from small to large, the degradation effect of Fe-Mn-NC-PDA (1.0) system on PCMX is first enhanced and then weakened. It may be that within a certain range, with the increase of PMS dosage, the sulfate radical (•SO4 - ) enrichment, improving the oxidation capacity of the system, but when excessive PMS is added, PMS will react with sulfate free radicals (•SO4 - ) reaction, consuming (•SO4 - ), producing low-activity •SO5 - , and excess sulfate radicals will produce •SO4 - The self-elimination reaction of the catalyst leads to poor effect. Then the degradation effect in different systems is investigated to explore the factors that really play the role of activation. Figure 8 It is known that Fe-Mn-NC-PDA (1.0), PMS and NC-PDA (1.0) have no degradation effect on PCMX when acting alone in the degradation process of PCMX, and it is also observed that NC-PDA (1.0) has no catalytic effect on PMS. In other words, the catalytic effect in the degradation process of PCMX is the iron and manganese ions loaded in Fe-Mn-NC-PDA (1.0) that activate PMS.

[0073] In order to further explore the mechanism of the reaction activator, we conducted electron paramagnetic resonance experiments. Fig. 9 As shown, no O2 was observed in the Fe-Mn-NC-PDA (1.0) system. - free radical signals, and 1 The O2 signal showed a downward trend compared with the control group, but DMPO was clearly observed. · -OH and DMPO · -SO4 - The signal of the adduct, but DMPO · The signal of -OH adduct can be derived not only from ·OH - Produces, some metal ions and SO4 ·- can also be produced, so we conducted sacrificial agent and PMSO experiments, such as Fig.10 As shown, add O2 - The quencher did not affect the performance, which is consistent with the EPR results, while the addition of OH - 、SO4 ·- When the quencher was removed, the system performance decreased slightly, indicating that the two free radicals only played a small role in the system. Strangely, when 1When O2 is used as the quencher, the system performance decreases significantly. Dimethyl sulfoxide (PMSO) is oxidized to the corresponding sulfone PMSO2 by Fe(IV) and Mn(IV) through the oxygen atom transfer step in acidic and neutral solutions, while ·OH - and SO4 ·- The induced product is a biphenyl compound, so PMSO can be used as a probe for Fe(IV) and Mn(IV). Fig.11 We can see that when 2.5 mg / L PMSO was added to the initial solution, about 80% of the consumed PMSO was converted into PMSO2 within 5 min, which indicates that Fe(IV) and Mn(IV) species exist in the system, and there are other ROS participating in the degradation of PMSO. From the above results, we infer that Fe(IV) and Mn(IV) are the main active species in the system, and 1 O2 may be an intermediate substance in their generation process, and its lifetime is extremely short, which leads to a decrease in the EPR signal. However, when FFA is used as its quencher, it can hinder the generation of Fe (IV) and Mn (IV), thereby leading to a decrease in the degradation effect.

[0074] Through HPLC-MS and literature analysis, 33 intermediates in this system were identified. Fig.12 The degradation pathway of PCMX in the Fe-Mn-PDA (1.0) / PMS system. Seven possible degradation pathways were analyzed. According to relevant literature, the benzene ring and phenolic hydroxyl group of PCMX are more susceptible to free radical attack. Path 4 is an addition reaction of the phenolic hydroxyl group attacked by free radicals. For paths 5, 6, and 7, the benzene ring of the PCMX molecule is attacked by free radicals and then undergoes ring opening and oxidation reaction to generate a variety of carboxylic acid substances. Path 1 is a degradation pathway in which PCMX is simultaneously oxidized and oxygen is added during dechlorination. Path 2 is a degradation pathway in which PCMX continues to be oxidized after dechlorination. Path 3 is an oxidation of the side chain of the benzene ring of PCMX to ketone. These intermediates continue to be oxidized under the action of ROSs, undergoing reactions such as dechlorination, ring opening, and oxidation of the side chain of the benzene ring to generate ketones, aldehydes, carboxylic acid substances, and small molecular organic matter, and are finally mineralized into water and carbon dioxide.

[0075] Although the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as limiting the present invention.

Claims

1. A method for preparing an iron-manganese bimetallic single atom-supported nitrogen-doped carbon sphere catalyst, comprising: 1) Disperse tris(hydroxymethylaminomethane) in deionized water to obtain a solution, adjust the pH of the solution to 8.4-8.6 with HCl, and name the obtained liquid Tris solution, wherein the concentration of tris(hydroxymethylaminomethane) is 50-55 mM; 2) Add a predetermined amount of dopamine hydrochloride to the Tris solution, wherein the mass and volume ratio of dopamine hydrochloride to the Tris solution is 1-2g:200ml, and heat under stirring. After the reaction is completed, wash the obtained sample with water and alcohol for several times, and dry it to obtain polydopamine powder; 3) Weigh a predetermined mass of the above polydopamine powder and disperse it into deionized water, add a predetermined mass of anhydrous manganese sulfate and nonahydrate ferric nitrate powder, wherein the ratio of polydopamine: anhydrous manganese sulfate: nonahydrate ferric nitrate is 1 g: 0.01 mmol: 0.01-0.03 mmol, mix well, centrifuge and remove the supernatant to obtain a solid sample, then freeze the sample for a predetermined time, and then freeze-dry in a vacuum; 4) Calcine the product of step 3 for a predetermined time under a protective atmosphere at a temperature of 800-850° C. to obtain an iron-manganese bimetallic single atom-supported nitrogen-doped carbon sphere catalyst.

2. The preparation method according to claim 1, wherein 6.057 g of tris(hydroxymethyl)aminomethane is weighed and dispersed into 1 L of deionized water, and the pH is adjusted to 8.

5.

3. The preparation method as claimed in claim 1, wherein 1.0 g of dopamine trihydrochloride is weighed and dispersed into 200 mL of Tris solution.

4. The preparation method according to claim 1, wherein in step 2, the heating temperature is 34-36°C and the heating time is 24-26 hours.

5. The preparation method according to claim 1, wherein in step 3, the mixture is vacuum dried in a freeze dryer for 24-36 hours.

6. The preparation method according to claim 1, in step 4, the calcination is carried out in a tubular furnace under argon protection at a rate of 3°C / min to 800°C and kept at that temperature for 4 hours.

7. An iron-manganese bimetallic single atom-loaded nitrogen-doped carbon sphere catalyst, wherein iron and manganese are loaded in the form of single atoms on the surface of nitrogen-doped carbon spheres obtained by thermal decomposition of polydopamine, characterized in that: The catalyst is prepared by the preparation method according to any one of claims 1 to 6.

8. A method for catalyzing p-chloro-meta-xylenol (PCMX) with the catalyst as claimed in claim 7, wherein the iron-manganese bimetallic single atom-loaded nitrogen-doped carbon sphere catalyst is placed in a container, and a p-chloro-meta-xylenol solution is added to the container, and PMS is added after stirring to degrade PCMX.

9. The method according to claim 8, wherein 10-20 mg of the above-mentioned iron-manganese bimetallic single atom-loaded nitrogen-doped carbon sphere catalyst is weighed and placed in a beaker, and 49-51 ml of para-chloro-meta-xylenol solution is added to the beaker and stirred, and then 5-15 mg of PMS is added to degrade PCMX.

Citation Information

Patent Citations

  • Preparation method and application of catalyst for treating organic wastewater

    CN115245836A